Pengaruh Usia Dan Religiusitas Terhadap Keyakinan Etis Pada Akuntan - Azhari Pratama; Herlina Helmy; Mayar Afriyenti (Universitas Negeri Padang, 2020)
This research aims to determine the effect of age and religiosity on accounting student this study also one to prove the differences the ethical beliefs between the beginning level of student. The sample selection in this study used a purposive sampling method. The population this study are where the accounting student all the university in Padang with is consisted of 3249 population. Respondents in this study consisted of 356 respondents obtained using the Slovin formula from the total population. Data collection techniques used in this study were questionnaires. The result should that age also proves effect on ethical beliefs in accountants with a tcount of 3.739 <ttable 1.960, it can be said that the first hypothesis was accepted. While the results of religiosity testing are known not to have a positive effect on the ethical beliefs of accountants. With the value of tcount -4,900> ttable 1,960 so it can be said that the second hypothesis is rejected. From the result of data processing it is also known that there are differences in ethical beliefs between beginning level students and final level students. This research also proves the concept theory moral cognitive Kohlberg